PENGUATAN PROFESIONALISME PENDIDIKAN AGAMA ISLAM DI ERA GLOBALISASI - Fitriah Khoirul Umamah; Asnawan (PT. Sulthan Journal Publisher, 2026)
Globalization has brought significant changes to the education system, social interaction patterns, and character development of students in the modern era. These conditions require Islamic Religious Education (PAI) teachers to have professionalism that is adaptive to technological developments, social change, and global cultural challenges. This study aims to analyze the professionalism of Islamic Religious Education (PAI) teachers in the era of globalization, including the position and role of Islamic Religious Education (PAI) teachers, the role of Islamic Religious Education (PAI) teachers in society, the relationship between Islamic Religious Education (PAI) teachers and students, and the challenges of Islamic Religious Education (PAI) teachers in facing the currents of globalization. The study used a qualitative approach with descriptive methods through literature reviews and historical analyses. Research data were obtained from various scientific articles, national and international journals, academic books, and other relevant scientific sources through academic databases such as Google Scholar and Garuda. Data analysis techniques were carried out through systematic data reduction, classification, interpretation, and content analysis. The results of the study indicate that Islamic Religious Education (PAI) teachers have a strategic position as educators, moral guides, agents of character formation, and mediators of religious values ​​amidst the dynamics of globalization. Islamic Religious Education (PAI) teachers also play an important role in society as role models and promoters of religious moderation. In their relationships with students, Islamic Religious Education (PAI) teachers function as learning facilitators, moral counselors, and spiritual guides. However, globalization presents various challenges in the form of digital technology development, moral degradation, foreign cultural influences, and low mastery of learning innovations among some teachers. Therefore, strengthening the professionalism of Islamic Religious Education (PAI) teachers through improving pedagogical competence, digital literacy, and developing religious character is a crucial need in facing 21st-century education. This study confirms that Islamic Religious Education (PAI) teacher professionalism is a fundamental element in building a generation that is religious, moderate, and globally competitive.